2017
DOI: 10.20853/31-4-894
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stigma and discrimination on sexual wellbeing of LGBTI students in a South African rural university

Abstract: Lesbian, gay, bisexual, transgender and intersex (LGBTI) students in South African institutions of Higher Education face stigma and discrimination. This is happening despite the country's constitution that prohibits any form of discrimination of an individual based on sexual orientation or gender identity. The study objective was to explore and describe the impact of stigma and discrimination on sexual-wellbeing of LGBTI students in a South African rural university. An interpretative phenomenological analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Most African countries criminalised same-sex relationship and considered the act as taboo (Mudavanhu, 2010 ), though Kenya and South Africa have constitutions that protect persons from exposure to stigma and discrimination based on sex (Ellis, 2009 ; Human Rights Watch, 2011 ). Mavhandu-Mudzusi ( 2017 ) reports about open condemnation of homosexuality by senior politicians and religious leaders in Zimbabwe, and people with such sexual orientation often suffer violence and aggression (Mabvurira, Motsi, Masuka, & Chigondo, 2012 ; Smith, 2015 ). The LGBTI community in South Africa faces considerable challenges which include social stigma, homophobic violence (particularly corrective rape) and high rates of HIV/AIDS infections, notwithstanding the South African constitution which outlawed discrimination based on sexual orientation, and legalised same-sex marriage (South African Government, 1996 ).While researching on ‘Impact of stigma and discrimination on sexual wellbeing of LGBTI students in a South African rural university’, Mavhandu-Mudzusi ( 2017 ) observed that LGBTI students at this university engage in diverse sexual practices.…”
Section: Introductionmentioning
confidence: 99%
“…Most African countries criminalised same-sex relationship and considered the act as taboo (Mudavanhu, 2010 ), though Kenya and South Africa have constitutions that protect persons from exposure to stigma and discrimination based on sex (Ellis, 2009 ; Human Rights Watch, 2011 ). Mavhandu-Mudzusi ( 2017 ) reports about open condemnation of homosexuality by senior politicians and religious leaders in Zimbabwe, and people with such sexual orientation often suffer violence and aggression (Mabvurira, Motsi, Masuka, & Chigondo, 2012 ; Smith, 2015 ). The LGBTI community in South Africa faces considerable challenges which include social stigma, homophobic violence (particularly corrective rape) and high rates of HIV/AIDS infections, notwithstanding the South African constitution which outlawed discrimination based on sexual orientation, and legalised same-sex marriage (South African Government, 1996 ).While researching on ‘Impact of stigma and discrimination on sexual wellbeing of LGBTI students in a South African rural university’, Mavhandu-Mudzusi ( 2017 ) observed that LGBTI students at this university engage in diverse sexual practices.…”
Section: Introductionmentioning
confidence: 99%
“…By responding to the WhatsApp questionnaire, participants provided tacit consent to participate in the study. By guaranteeing anonymity, the principal researcher relied on her experience of working with LGBTIQ+ individuals in rural areas, where many were loath to inform anyone outside of the LGBTIQ+ group, including healthcare professionals, that they were gender non-conforming, for fear that their status would be revealed to their parents/family, which would have the negative consequences of being banished from home, or forced into marriage or parenting (Mavhandu-Mudzusi, 2017; 2018b).…”
Section: Methodsmentioning
confidence: 99%
“…Research shows that heteronormativity is evident at some universities, and that it often perpetuates stigma, prejudice and homophobia against LGBTIQ+ students, who are often socially excluded (Kiguwa & Langa, 2017;Mavhandu-Mudzusi, 2017;Mavhandu-Mudzusi et al, 2015;Nduna et al, 2017;Smuts et al, 2015). In a quantitative study conducted by Smuts et al (2015) at a South African university, it was found that homophobia amongst students is often informed by earlier heteronormative socialization, which was backed up by religious teachings that the students grew up under.…”
Section: Heteronormativity and Homophobia In Universitiesmentioning
confidence: 99%
“…This paper explores the factors that influence perceptions that university undergraduate students hold concerning religiously sanctioned homophobia. While some research has been done on homophobia in South African universities (Kiguwa & Langa, 2017;Lesch et al 2017;Mavhandu-Mudzusi, 2017;Mayeza, 2021), much of the research is qualitative, and it usually focuses on the experiences of LGBTIQ+ students, without paying attention to the perceptions of the broader student community. This study seeks to provide a quantitative account of undergraduate university students' perceptions of religiously sanctioned homophobia.…”
Section: Introductionmentioning
confidence: 99%